Australian rural community aged care services: Precarity and capacity. Issue 2 (3rd May 2021) - Savy, Pauline; Hodgkin, Suzanne
Abstract: In Australia, the precarity of the aged care sector has been well documented over several decades. During this time, policy reforms have ultimately landed care, and the business of providing it, within a market model. Following recent evidence produced by the Royal Commission into Aged Care and Safety and the COVID‐19 Senate Committee, this model and the sector's incapacity to consistently deliver appropriate care has been the subject of intense public scrutiny and debate. The many COVID‐19‐related deaths of aged care residents have added to demands for urgent action to redress the sector's weaknesses, particularly those relating to workforce adequacy. This paper presents findings from a recent mixed methods study of community aged care provision by five providers who operate across a large rural part of regional Victoria. It utilises data to illustrate the impact of rural location on care provision, and significantly, on local capacity to maintain an appropriately skilled workforce. Demographic factors and funding shortfalls for consumers with multiple, complex care needs underscore the need for strategic planning to ensure workforce adequacy into the future. Encouragingly, our data showcase the many capacities of community aged services in this rural area and the opportunity to develop effective strategies relative to the recruitment and retention of direct care workers and the design of best practice models for meeting complex care needs. Abstract : In Australia, the precarity of the aged care sector has been well documented over several decades. This paper provides findings from a mixed methods study conducted in rural Victoria. The data showcase the many capacities of rural community aged care providers and the opportunities for effective workforce strategies.